B cell activation via immunometabolism in systemic lupus erythematosus - Iwata, Shigeru; Hajime Sumikawa, Maiko; Tanaka, Yoshiya (Frontiers in Immunology, 2023)
Systemic lupus erythematosus (SLE) is an inflammatory autoimmune disease involving multiple organs in which B cells perform important functions such as antibody and cytokine production and antigen presentation. B cells are activated and differentiated by the primary B cell receptor, co-stimulatory molecule signals—such as CD40/CD40L—, the Toll-like receptors 7,9, and various cytokine signals. The importance of immunometabolism in the activation, differentiation, and exerting functions of B cells and other immune cells has been widely reported in recent years. However, the regulatory mechanism of immunometabolism in B cells and its involvement in SLE pathogenesis remain elusive. Similarly, the importance of the PI3K-Akt-mTOR signaling pathway, glycolytic system, and oxidative phosphorylation has been demonstrated in the mechanisms of B cell immunometabolic activation, mainly in mouse studies. However, the activation of the mTOR pathway in B cells in patients with SLE, the induction of plasmablast differentiation through metabolic and transcription factor regulation by mTOR, and the involvement of this phenomenon in SLE pathogenesis are unclear. In our studies using activated B cells derived from healthy donors and from patients with SLE, we observed that methionine, an essential amino acid, is important for mTORC1 activation. Further, we observed that splenic tyrosine kinase and mTORC1 activation synergistically induce EZH2 expression and plasmablasts by suppressing BACH2 expression through epigenomic modification. Additionally, we identified another mechanism by which the glutaminolysis-induced enhancement of mitochondrial function promotes plasmablast differentiation in SLE. In this review, we focused on the SLE exacerbation mechanisms related to the activation of immune cells—especially B cells—and immunometabolism and reported the latest findings in the field.